Estabilidade fenotípica de genótipos de algodoeiros obtidos por semigamia no Estado de Minas Gerais - Silva, Petrônio José da (2008)
The objectives of this research were: to evaluate the performance of doublehaploid cotton genotypes (HD) in relation to their parental genotypes in three contrasting environments of the state of Minas Gerais, Brazil, and to determine the possible genotype by environment interactions and stability and adaptability parameters. In the state of Minas Gerais, Brazil, the cotton growing regions present a wide environmental variation. The field trials were conducted in the 2006/2007 growing season, at three representative locations of the regions: Triângulo Mineiro (Uberaba), Alto Paranaíba (Patos de Minas) and North (Nova Porteirinha). The experimental design used was the complete randomized-block, with five replications. The data collected for the main characters of economic importance (agronomic and fiber properties) were analyzed for each location as well as for the three locations, by means of the software GENES. Analyses of adaptability and stability were performed, when pertaining, by the methods of Annicchiarico (1992) and Lin & Binns (1988). No significant GxE interactions were found for the great majority of the characters evaluated. The double-haploids presented, in average, improved performance over their original parents in the three environments and thus the technique of haploid chromosome complement doubling did not induced negative effects (inbreeding depression). The double-haploids were, in general, more stable than the parental genotypes they were derived of, which demonstrated that the semigamy method is efficient and promising for the development of new genotypes. It was not confirmed the hypothesis that the high levels of expected homozygosis of the DH genotypes could imply lesser stability over different environments. In the location of Uberaba, the DH genotypes in general presented smaller variation than their respective parents for the traits evaluated, thus confirming the efficiency of the method. The DH-EPAMIG-4 was more variable than its parent as well as than the other DH genotypes. The locations were quite contrasting in terms of environment and therefore were representative of the cotton growing regions of the state.